Evaluation of acupressure effects on self-efficacy and pregnancy rate in infertile women under in vitro fertilization/intracytoplasmic sperm injection treatment: A randomized controlled trial - Maryam Hassanzadeh Bashtian; Talat Khadivzadeh; Shapour Badiee Aval; Habibollah Esmaily (Journal of Education and Health Promotion, 2018)
Context: Infertility is one of the major stressful events in individual life, especially women. Self-efficacy means a person can perceive a potentially threatening and stressful situation as being amenable to influences of personal control. Aims: This study was conducted to determine the acupressure effects on self-efficacy and pregnancy rate in infertile women under in vitro fertilization (IVF)/intracytoplasmic sperm injection treatment. Settings and Design: This study was a randomized controlled trial in infertile women. It performed at Milad IVF Center, Mashhad, Iran, from September 2015 to August 2016. Materials and Methods: The sample size was 144 participants. The participants were randomly divided into three groups: real and sham acupressure and control groups. Acupressure performed on the H7 and P6 acupoints on both the hands. The infertility self-efficacy scale was completed before and after intervention. Beta-human chorionic gonadotropin hormone assay was measured to determine pregnancy. Data analysis was done by Chi-square, Fisher's exact, paired sample t, Kruskal–Wallis, and ANOVA test and general linear model and multinomial logistic. Levels of significance were reported at P < 0.05. Results: The mean age of women was 30.84 ± 5.34 years. The ovulation factor (P = 0.02) and spouse's job (P = 0.05) were statistically significant difference between the groups. The score of self-efficacy and frequency of clinical pregnancy were no significant difference among three groups. Using linear regression, only the score of primary self-efficacy (before intervention) was in a significant relationship with self-efficacy after the intervention (P < 0.001). Conclusion: To our results, we recommend more research for assessing acupressure effects on self-efficacy and clinical pregnancy rate in infertile women.